Resource mapping during a natural disaster: A case study on the 2015 Nepal earthquake. (September 2017) - Basu, Moumita; Ghosh, Saptarshi; Jana, Arnab; Bandyopadhyay, Somprakash; Singh, Ravikant
Abstract: Any major natural disaster, such as an earthquake, is accompanied by an urgent need for various types of resources in the disaster-affected region, which primarily includes medical resources, human resources, and infrastructural resources. How quickly this need for resources can be satisfied might critically determine the extent of damage and human casualties in the aftermath of the disaster. Hence, knowledge about what type of resources are usually needed in the aftermath of a disaster is important for responding organizations for planning formative solutions, to be better prepared to mitigate any upcoming disaster. The goal of this study is to curate the resource needs during a major disaster – the earthquake in Nepal and parts of India in April 2015. This work has been carried out in association with Doctors For You (DFY), a humanitarian organization of medical professionals who work in various disasters-affected regions. A large set of WhatsApp messages exchanged among DFY members who were working in the disaster-affected areas of Nepal was collected and analyzed to identify the different resource requirements and the corresponding delay in the mobilization of such resources. The study revealed detailed phase-wise requirement of various types of resources and also suggested that for several resources, there was a significant delay between the requirement and the actual availability of the resources. The acumens from this study will not only help disaster risk management in Nepal but also help in preparedness planning in other earthquake-prone regions of the world. Highlights: This study is based on WhatsApp messages exchanged among medical professionals in the aftermath of 2015 Nepal earthquake. The study assimilates knowledge about phase-wise requirements of various types of resources in the aftermath of a disaster. Such knowledge can help government agencies and first responders to be better prepared to mitigate any upcoming disaster. Real-time analysis of such data would assist decision makers in forming resource mapping strategies dynamically.